No more magic - Avi, 1937- (New York : Yearling, 2000)
While searching for his bicycle that disappeared on Halloween, a young boy and his two friends become involved in a magic adventure.
"A Yearling book.".
3.7
4.4.
3-6
Keywords: Detective and mystery stories; Magic -- Juvenile Fiction; Detective and mystery stories; Magic -- Fiction; Magic -- Fiction; Mystery fiction